Inflammatory myofibroblastic tumor of renal pelvis presenting with iterative hematuria and abdominal pain: A case report - WU, SHUIQING (Oncol Lett, 2015)
Inflammatory myofibroblastic tumor (IMT) is a rare type of mesenchymal tumor, which may affect various organs. The preferential site for IMT in the genitourinary system is the urinary bladder, while the presence of IMT in the kidney, and particularly in the renal pelvis, is rare. In the present report, the case of a 43-year-old man who was admitted to the Department of Urology of The Second Xiangya Hospital of Central South University (Changsha, China) in July 2012, with complaints of iterative gross hematuria and abdominal pain unresponsive to antibiotics is described. Computed tomography and magnetic resonance imaging indicated a slightly enhanced mass in the left renal pelvis of 1.5 cm in diameter. On request of the patient, a left nephrectomy was then performed, based on a suspected diagnosis of renal pelvic carcinoma. However, analysis of the intraoperative fast-frozen section exhibited proliferation of compact spindle cells, suggesting IMT. Therefore, further ureterectomy was avoided, and the patient remained in healthy condition thereafter.